Integrated modeling of hydrological processes and groundwater recharge based on land use land cover, and climate changes: a systematic review - Mensah, J. K.; Ofosu, Eric Antwi; Yidana, S. M.; Akpoti, Komlavi; Kabo-bah, A. T. (Elsevier, 2022)
Groundwater is the main available freshwater resource and therefore its use, management and sustainability are closely related to the Sustainable Development Goals (SDGs). However, Land Use Land Cover (LULC) and climate change are among the factors impacting groundwater recharge. The use of land-use and climate data in conjunction with hydrological models are valuable tools for assessing these impacts on river basins. This systematic review aimed at assessing the integrated modeling approach for evaluating hydrological processes and groundwater recharge based on LULC and climate change. The analysis is based on 200 peer-reviewed articles indexed in Scopus, and the Web of Science. Continuous research and the development of context-specific groundwater recharge models are essential to increase the long-term viability of water resources in any basin. The long-term impacts of natural and anthropogenic drivers on river basin interactions require integrating knowledge and modeling capabilities across biophysical responses, environmental problems, policies, economics, social, and data.